2022
DOI: 10.1002/smtd.202200827
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Morphological Characterization of Coordinated Binder and Solid Electrolyte Interphase in Silicon‐Based Electrodes for Li‐Ion Batteries

Abstract: amount of lithium alloyed with silicon (up to Li 3.75 Si) compared to lithium intercalated in graphite (up to LiC 6 ). However, the silicon volume expansion induced by its lithiation is much higher, up to 280% versus 10% for graphite. [1] This translates to electrode morphology instability during cycling at different scales: i) at the micrometer scale, upon binder bridge breakage, either between particles or between particles and the current collector, which lead to the appearance of cracks and delamination, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 45 publications
5
15
0
Order By: Relevance
“…In fact, the main reduction peak(s) on the d Q /d V curves at 0.9–1.1 V (vs Li + /Li 0 ) seen for both formulations is associated with the reduction of FEC. ,, Interestingly, this phenomenon is more intense for formulations without Zn, which tends to confirm that the coordination with Zn increases the ability of the binder to act as an artificial passivation (SEI) layer. This result is in complete agreement with our previous STEM-EDX study on ZnSO 4 -containing electrodes after one cycle, which evidenced that the surface of the silicon particles covered by the binder (including Zn) are exempt of standard inorganic SEI components (containing F and P) …”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In fact, the main reduction peak(s) on the d Q /d V curves at 0.9–1.1 V (vs Li + /Li 0 ) seen for both formulations is associated with the reduction of FEC. ,, Interestingly, this phenomenon is more intense for formulations without Zn, which tends to confirm that the coordination with Zn increases the ability of the binder to act as an artificial passivation (SEI) layer. This result is in complete agreement with our previous STEM-EDX study on ZnSO 4 -containing electrodes after one cycle, which evidenced that the surface of the silicon particles covered by the binder (including Zn) are exempt of standard inorganic SEI components (containing F and P) …”
Section: Resultssupporting
confidence: 92%
“…We recently demonstrated that such a coordinated CMC/CA/Zn(II) binder acts, at least partially, as an artificial SEI. 19 We here show that such bonds have also a beneficial impact on the electrode's mechanical properties as evidenced by scratch tests and nanoindentation experiments. The invariability of the mechanical properties (hardness and elastic modulus) of the cross-linked binder in the presence of the electrolyte, unlike the uncross-linked binder, is also demonstrated.…”
Section: ■ Introductionmentioning
confidence: 59%
See 3 more Smart Citations